ANALISIS SEASONED EQUITY OFFERINGS (SEO) TERHADAP PENURUNAN KINERJA PASCA PENAWARAN (Studi Kasus Pada Perusahaan Yang Terdaftar di BEJ Periode 2000-2002) - Susanto, Barkah Susanto; Handrisaktiyati, Vian Handrisaktiyati (Universitas Muhammadiyah Magelang, 2005)
Performance declining after seasoned equity offerings can be explained by agency theory and windows of opportunity concepts. Those concept show the management opportunistic behavior because of asymmetric information happened between manager and investor before offering. However, that condition can not be defended and make the performance declining in the long term both in financial and stock performances. This reased will prove the declining of performance because of management opportunistic behavior. This research uses the datas of firms which do the seasoned equity offerings on Jakarta Stock Exchange, in 2000-2002 periods. Using the normalitas datas, descriptive statistic and paired sampel t-test as the proxy of management opportunistic hebavior is measured to prove that prejudise.